Layanan Bimbingan Konseling Untuk Siswa MI Darun Najah Desa Ngemplak Kidul Kecamatan Margoyoso Kabupaten Pati - Nisaidah, Choirun; Khoiriyyah, Nurul; Fajari, M. Ahris Nur; Lathuba, Siti Khulaila; Muhjayani, Endang; Nashiruddin, Ahmad (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
Counseling Guidance is a unit that exists in every educational institution from kindergarten to university. BK services not only help students who have problems, but also help them to find their maximum potential. Therefore, the researcher is interested in conducting research at MI Darun Najah Ngemplak Kidul Pati to find out the implementation of guidance and counseling activities there as well as the problems experienced by the students and the factors that cause them. The purpose of this study is to find out the implementation of the student counseling guidance service program at MI Darun Najah Ngemplak Kidul Pati. This type of research is a field research with a qualitative descriptive approach. The results of the study concluded that the implementation of counseling guidance services for students at MI Darun Najah Ngemplak Kidul Pati was implemented through student affairs, homeroom teachers, and classroom teachers with the implementation of various counseling guidance programs, these programs ranging from orientation, cooperation, health, information, learning, individual, and periodic.